GREEN GROWTH FINANCING - Khutorova, Natalia; Shalaev, Valentin (Innovation in Woodworking Industry and Engineering design, 2014)
This article describes the definition of green finance as the broad range of funding for environment-oriented technologies, projects, industries or businesses. There is the analyze of the state of green financemarket. The problems and prospects are identified. It was noted the increasing role of financial instruments in the transition to low-carbon and climate-resilient development.The conclusion is: greening economic growth is the only way in which sustainable, inclusive development can be achieved. Many countries have seen the benefits of green growth, and developing countries are taking a clear leadership role in various low carbon initiatives and are using domestic policy mechanisms.